Marketing Success through Holistic Branding - Upadhyaya, Makarand; Soni, Swati (Indian Journal of Marketing, 2006)
A brand is a claim of distinction. A claim of distinction helps a brand stand out of clutter and provides the customer a clear reason to choose the brand over the competitor’s offerings. Brand building is a costly exercise. In a survey of marketing executives, 85% were indicative of the fact that marketing efforts fail because marketing department is the only group behind all the initiatives and efforts. This has to be replaced by a holistic solution for brand development, i.e. every individual throughout the organization needs to be on- board in an exercise of such magnanimity. This claim of distinction should be generously supported in every aspect of, and interaction with your brand.